Analisis Efektifitas Gaya Kepemimpinan Situasional Di Lingkungan Organisasi Era 4.0 - Ramadhan, Ihsan Fauzi; Fitriani, Novita Badra; Zakia, Hudan Gulaman; Hermawati, Sheni Pratiwi; Sahwaludin, Taufik Hidayat (Universitas Pahlawan Tuanku Tambusai, 2024)
The 4.0 era is characterized by rapid technological advances and dynamic changes in the business environment, demanding adaptive and flexible leadership styles. This article analyzes the effectiveness of situational leadership styles in modern organizations, focusing on how leaders can adjust their approach based on the situation and team needs and with the research methods used including case studies, surveys, and interviews with leaders in various industries. The results show that effective situational leadership can improve team performance, innovation, and organizational adaptability. Factors such as technology utilization, organizational culture, and team dynamics play an important role in the successful implementation of this leadership style